Dexmedetomidine as an Adjuvant to Analgesic Strategy During Vaso‐Occlusive Episodes in Adolescents with Sickle‐Cell Disease. Issue 8 (23rd July 2015) - Sheehy, Kathy A.; Finkel, Julia C.; Darbari, Deepika S.; Guerrera, Michael F.; Quezado, Zenaide M. N.
Abstract: Patients with sickle‐cell disease (SCD) can experience recurrent vaso‐occlusive episodes (VOEs), which are associated with severe pain. While opioids are the mainstay of analgesic therapy, in some patients with SCD, increasing opioid use is associated with continued and increasing pain. Dexmedetomidine, an α2 ‐adrenoreceptor agonist with sedative and analgesic properties, has been increasingly used in the perioperative and intensive care settings and has been shown to reduce opioid requirement and to facilitate opioid weaning. Therefore, there might be a role for dexmedetomidine in pain management during VOEs in patients with SCD. Here, we present the hospital course of 3 patients who during the course of VOEs had severe pain unresponsive to opioids and ketamine and were treated with dexmedetomidine. Dexmedetomidine infusions that lasted for 3 to 6 days were associated with marked reduction in daily oral morphine‐equivalent intake and decreases in pain scores (numeric rating scale). There were no hemodynamic changes that required treatment with vasoactive or anticholinergic agents. These preliminary findings of possible beneficial effects of dexmedetomidine in decreasing opioid requirements support the hypothesis that dexmedetomidine may have a role as a possible analgesic adjuvant to mitigate VOE‐associated pain in patients with SCD.